The effect of idiosyncratic shocks on labor market outcomes of informal households in Indonesia - Santoso, Rokhedi Priyo; Sriyana, Jaka (Penerbit Universiti Kebangsaan Malaysia, 2020)
The informal households are considered to be the most vulnerable to any idiosyncratic shocks rather than the formal ones. Unfortunately, the established literatures mostly do not specifically emphasize the analysis of this group. This study contributes to literatures on the specific analysis on the effects of idiosyncratic shocks namely sickness, death, and job loss on the labor market outcomes of informal households in Indonesia. The analytical method used is the estimation of panel data with a fixed-effect model to control for unobserved heterogeneity. The data consists of 3,755 informal households taken from Indonesia Family Life Survey (IFLS) in the period of 2007/2008 and 2014/2015. Estimated results indicate that illness and job loss significantly reduce earning of self-employed households, while the number of working hours remains unchanged. On the other hand, the working hours of causal households in agriculture significantly increase when a family member is sick. Even though they work longer, their earning remains constant. These findings indicate that shocks cause a significant decline in the economic welfare of the informal households in Indonesia.